PSIV-6 Effect of a Phytogenic Water Additive on Growth Performance, Blood Metabolites and Gene Expression of Amino Acids Transporters in Nursery Pigs Fed with Low Protein Diets. (30th November 2020) - Shili, Cedrick N; Habibi, Mohammad; Sutton, Julia; Barnes, Jessie; Burchkonda, Jacob; Siahaan, Doris; Pezeshki, Adel
Abstract: Moderately low protein (MLP) diets can help decrease nutrient excretion from the swine production. However, MLP diets negatively impact growth performance. We hypothesized that supplementing MLP diets with phytogenics may reduce the negative effects of these diets on growth. The objective of this study was to investigate the effect of a phytogenic water additive (PWA; Herbanimal ® ) on growth performance, blood metabolite and gene expression of amino acids transporters in pigs fed with MLP diets. Forty-eight weaned barrows were allotted to six dietary treatments (n = 8) for 4 weeks: >CON-NS: standard protein diet-no PWA; CON-LS: standard protein diet-low PWA dose (4 ml/L); CON-HS: standard protein diet-high PWA dose (8 ml/L); LP-NS: low protein diet-no PWA; LP-LS: low protein diet-low PWA dose (4 ml/L); LP-HS: low protein diet- high PWA dose (8 ml/L). Feed intake and body weight were recorded daily and weekly, respectively. At week 4, blood and tissue samples were collected and analyzed for metabolites using a chemistry analyzer and amino acid transporters using qPCR, respectively. The data were analyzed by univariate GLM (SPSS ® ) and the means were separated using paired Student's t-test corrected by Benjamini-Hochberg. Pigs fed CON-HS improved the average daily gain and serum calcium and phosphorus concentrations compared to CON-NS. Pigs fed LP-LS had higher serum phosphorus and blood urea nitrogen compared to the pigs fed with LP-NS. The mRNA abundance of SLC7A11 in the jejunum was lower in CON-LS and CON-HS compared to CON-NS. Additionally, mRNA abundance of SLC6A19 in the jejunum of pigs fed with LP-LS was higher compared to LP-NS and lower in CON-HS relative to pigs fed with CON-LS. In conclusion, PWA improved the growth performance of pigs fed standard protein diets but not low protein diets. Further, the PWA improved the concentrations of blood calcium and phosphorous in pigs fed MLP diets. Funding: Agrivida and Animal Health and Production and Animal Products: Improved Nutritional Performance, Growth, and Lactation of Animals from the USDA-NIFA.